Unraveling the mysteries of serum albumin—more than just a serum protein - Merlot, Angelica M.; Kalinowski, Danuta S.; Richardson, Des R. (Frontiers in Physiology, 2014)
Serum albumin is a multi-functional protein that is able to bind and transport numerous endogenous and exogenous compounds. The development of albumin drug carriers is gaining increasing importance in the targeted delivery of cancer therapy, particularly as a result of the market approval of the paclitaxel-loaded albumin nanoparticle, Abraxane®. Considering this, there is renewed interest in isolating and characterizing albumin-binding proteins or receptors on the plasma membrane that are responsible for albumin uptake. Initially, the cellular uptake and intracellular localization of albumin was unknown due to the large confinement of the protein within the vascular and interstitial compartment of the body. Studies have since assessed the intracellular localization of albumin in order to understand the mechanisms and pathways responsible for its uptake, distribution and catabolism in multiple tissues, and this is reviewed herein.